The Role of Gus and Yuk Tourism Ambassadors in The Promotion of Cultural Tourism in Mojokerto District - Sukma, Devita Candra; Febriana, Poppy (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
Mojokerto Regency in East Java is a developing area thanks in large part to investment in new transportation, other facilities and cultural tourism. As Tourism Ambassadors for the Mojokerto Regency Tourism and Creative Economy Office, Gus and Yuk play an important role in introducing and promoting the tourism potential of Mojokerto Regency to a wide audience. This research aims to study how tourism ambassadors can help improve tourism promotion in Mojokerto Regency. The research was conducted at the Mojokerto Regency Cultural Tourism Office. This article's research method was achieved through the use of descriptive qualitative analysis techniques. In which the author conducted an organized interview about the functions played by tourism ambassadors in the cultural tourism industry. The information used in this research comes from a variety of sources, including books and articles, as well as interviews with experts in the field who have direct knowledge of the problem under study.